Current development, potentials, and challenges of biological synthesis of nanoparticle (as a photocatalyst): A review. Issue 1 (December 2020) - Agustina, L; Suprihatin, S; Romli, M; Suryadarma, P
Abstract: Nanoparticles can be applied potentially in various areas of industrial processes because of their unique mechanical and optical properties, antimicrobial abilities, and catalytic capabilities. This paper aims to analyze the current status of research and development of producing high-value nanoparticles as a photocatalyst using the principle of green chemistry and to identify the potentials and challenges of the new green synthesis in its further developments. The biological method is considered effective and environmentally friendly in producing nanoparticles as a photocatalyst. These efforts can be realized by utilizing natural reducing agents. The bioreductor compounds are available in plants and their waste is in large quantities. It is also reported that some kinds of microorganisms may be used in the biological synthesis of nanoparticles effectively. Some potentials and challenges for it, further research and development were identified, presented, and discussed. Biologically, the synthesis of nanoparticles is considered to be more energy efficient because the process is simpler by utilizing microorganisms, plants and horticultural food waste extracts as a medium for the synthesis of nanoparticles.